Pengaruh Media Exposure, Ukuran Perusahaan, Profitabilitas, dan Leverage Terhadap Carbon Emission Disclosure - Tri Maya Utari; Vita Aprilina (JRAK: Journal of Accounting Research and Computerized Accounting, 2023)
The purpose of this study is to analyze the effect of media exposure, company size, profitability, and leverage on carbon emission disclosures. This research is research using descriptive methods with quantitative analysis using secondary data. The sample for this research is non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The sampling technique in this study was purposive sampling. The independent variables used in this study are the Effect of Media Exposure, Firm Size, Profitability, and Leverage. The dependent variable used in this study is Carbon Emission Disclosure. The data analysis technique used is multiple linear analysis. By processing data using Eviews 9. Based on the test results, media exposure and leverage have a positive effect on carbon emission disclosure. While company size and profitability have no effect on carbon emission disclosure. So with this, it is hoped that the next researcher can add other independent variables that are not used in this research. Keywords: Media Exposure, Company Size, Profitability, Leverage, Carbon Emission Disclosure.